Clinical correlates and outcomes in a group of Puerto Ricans with systemic lupus erythematosus hospitalized due to severe infections. (21st May 2018) - Jordán-González, Patricia; Shum, Lee Ming; González-Sepúlveda, Lorena; Vilá, Luis M
Objective: Infections are a major cause of morbidity and mortality in systemic lupus erythematosus. Clinical outcomes of systemic lupus erythematosus patients hospitalized due to infections vary among different ethnic populations. Thus, we determined the outcomes and associated factors in a group of Hispanics from Puerto Rico with systemic lupus erythematosus admitted due to severe infections. Methods: Records of systemic lupus erythematosus patients admitted to the Adult University Hospital, San Juan, Puerto Rico, from January 2006 to December 2014 were examined. Demographic parameters, lupus manifestations, comorbidities, pharmacologic treatments, inpatient complications, length of stay, readmissions, and mortality were determined. Patients with and without infections were compared using bivariate and multivariate analyses. Results: A total of 204 admissions corresponding to 129 systemic lupus erythematosus patients were studied. The mean (standard deviation) age was 34.7 (11.6) years; 90% were women. The main causes for admission were lupus flare (45.1%), infection (44.0%), and initial presentation of systemic lupus erythematosus (6.4%). The most common infections were complicated urinary tract infections (47.0%) and soft tissue infections (42.0%). In the multivariate analysis, patients admitted with infections were more likely to have diabetes mellitus (odds ratio: 4.20, 95% confidence interval: 1.23–14.41), exposure to aspirin prior to hospitalization (odds ratio: 4.04, 95% confidence interval: 1.03–15.80), and higher mortality (odds ratio: 6.00, 95% confidence interval: 1.01–35.68) than those without infection. Conclusion: In this population of systemic lupus erythematosus patients, 44% of hospitalizations were due to severe infections. Patients with infections were more likely to have diabetes mellitus and higher mortality. Preventive and control measures of infection could be crucial to improve survival in these patients.